Hybrid Clinical and Histopathological Pattern in Annular Lesions: An Overlap between Annular Elastolytic Giant Cell Granuloma and Granuloma Annulare? - Oliveira, Felipe Ladeira de (2012)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Rio de Janeiro, RJ. Brasil.